Elixir of the Service Quality of Islamic Banking Sector in Bangladesh (Global Journal of Management and Business Research, 2016)
Islamic Banking Sector (IBS) is the most influential domain in the economic development of Bangladesh. In the 21 st century, IBS has passed thirty years glorious journey creating huge competition considering its service quality and achieved a remarkable growth. Service Quality (SQ) is the most significant affecting factor for remarkable growth of IBS in Bangladesh from 1983 to 2013. Thus, this research work attempts to determine the elixir of the service quality of Islamic Banks existed in Bangladesh as Islamic Banking Sector using Structural Equation Modelling (SEM). This research uses modified CARTER model (Compliance of Islamic Shariah, Reliability, Assurance, Tangibility, Empathy and Responsiveness) consisting of 34 (thirty four) dimensions with 6 (six) constructs. A total of 396 samples have been used from 6 (six) full pledged Islamic banks in Bangladesh. This study reveals that 20 (twenty) factors have found as the elixir of service quality of Islamic banks in Bangladesh where assurance is the most significant construct followed by reliability, tangibility, empathy, responsiveness and tensely compliance of Islamic Shariah.
Keywords: islamic banking sector (IBS); elixir; service quality (SQ); carter; and vision-21